Recent recruiting trends and their implications for models of enlistment supply - Murray, Michael P., 1946- (RAND, 1999)
The authors estimate an econometric model of high-quality enlistment supply using geographically disaggregated data from two periods, FY83-87 and FY90-93. They find that econometric models based on data from the earlier period do not predict the recruiting difficulties reported by the military in the 1990s. This conforms to a preliminary assessment provided by Asch and Orvis (MR-549-A/OSD, 1994). The authors also find that econometric models estimated with the 1990s data give altered counsel about the effects of at least some policy variables, most notably the number of recruiters.